Graduate Study in Education at Kansas State University - J. Harvey Littrell (Educational Considerations, 1975)
The most significant changes in the College of Education have occurred in the area of graduate study. New graduate programs in late afternoon and evening, as well as eight off-campus locations, have extended the program to serve the teachers of Kansas. In addition K-State is cooperating with a consortium of southern and midwestern colleges to strengthen programs and faculty for developing institutions. Graduate study in education is just one more example of the land-grant philosophy which brings the resources of the university to the people it serves.